The house of silk : a Sherlock Holmes novel - Horowitz, Anthony (New York : Mulholland Books, 2011)
It is 1890. A year after Holmes's death, Watson--now in a retirement home--narrates a tale of Sherlockian detection that could tear apart the very fabric of society. The story opens with a train robbery in Boston, and moves to the innocuous setting of Wimbledon.
Angela Misa
Keywords: Private investigators -- England -- Fiction; London (England) -- Fiction